The purple acid phosphatase GmPAP21 enhances internal phosphorus utilization and possibly plays a role in symbiosis with rhizobia in soybean. Issue 2 (2nd December 2016) - Li, Chengchen; Li, Caifeng; Zhang, Haiyan; Liao, Hong; Wang, Xiurong
Abstract : Induction of secreted and intracellular purple acid phosphatases (PAPs; EC 3.1.3.2) is widely recognized as an adaptation of plants to phosphorus (P) deficiency. The secretion of PAPs plays important roles in P acquisition. However, little is known about the functions of intracellular PAP in plants and nodules. In this study, we identified a novel PAP gene GmPAP21 in soybean. Expression of GmPAP21 was induced by P limitation in nodules, roots and old leaves, and increased in roots with increasing duration of P starvation. Furthermore, the induction of GmPAP21 in nodules and roots was more intensive than in leaves in both P‐efficient genotype HN89 and P‐inefficient genotype HN112 in response to P starvation, and the relative expression in the leaves and nodules of HN89 was significantly greater than that of HN112 after P deficiency treatment. Further functional analyses showed that over‐expressing GmPAP21 significantly enhanced both acid phosphatase activity and growth performance of hairy roots under P starvation condition, indicating that GmPAP21 plays an important role in P utilization. Moreover, GUS expression driven by GmPAP21 promoter was shown in the nodules besides roots. Overexpression of GmPAP21 in transgenic soybean significantly inhibited nodule growth, and thereby affected plant growth after inoculation with rhizobia. This suggests that GmPAP21 is also possibly involved in regulating P metabolism in nodules. Taken together, our results suggest that GmPAP21 is a novel plant PAP that functions in the adaptation of soybean to P starvation, possibly through its involvement in P recycling in plants and P metabolism in nodules.